Brown Adipose Tissue Growth and Development - Michael E. Symonds (Scientifica)
Brown adipose tissue is uniquely able to rapidly produce large amounts of heat through activation of uncoupling protein (UCP) 1. Maximally stimulated brown fat can produce 300 watts/kg of heat compared to 1 watt/kg in all other tissues. UCP1 is only present in small amounts in the fetus and in precocious mammals, such as sheep and humans; it is rapidly activated around the time of birth following the substantial rise in endocrine stimulatory factors. Brown adipose tissue is then lost and/or replaced with white adipose tissue with age but may still contain small depots of beige adipocytes that have the potential to be reactivated. In humans brown adipose tissue is retained into adulthood, retains the capacity to have a significant role in energy balance, and is currently a primary target organ in obesity prevention strategies. Thermogenesis in brown fat humans is environmentally regulated and can be stimulated by cold exposure and diet, responses that may be further modulated by photoperiod. Increased understanding of the primary factors that regulate both the appearance and the disappearance of UCP1 in early life may therefore enable sustainable strategies in order to prevent excess white adipose tissue deposition through the life cycle.